(untitled) (West African Journal on Sustainable Development, 2024)
Over the years, various unions in the industrial sector have deployed strikes or industrial actions as a tool to compel the ruling class to yield to their demands and implement agreements they willingly endorsed. Though, strikes impacts the public universities perniciously, and detrimental to the actualization of educational goals as enshrined in the sustainable development goals (SDGs); regrettably, Nigerian government appears rather adamant about resolving the issues that necessitate strikes as well as forestall their escalation. This is really the situation the Academic Staff Union of Universities (ASUU) has faced over the years, in the hands of Nigerian government; who had vehemently and consistently reneged on its promises with utter bravado. Suffice that the agreements do not only bother on the welfare of workers and students alike but also towards the rapid development of Nigerian education system and stabilization of the economy. Unfortunately, government’s blatant refusal to implement agreements had compelled the union to incessantly embark on strikes, spanning from weeks to months with their attendant effects, such as disruption of academic activities on campuses, suspension of statutory meetings, withholding of workers’ salaries to mention but a few. Consequently, while some students get frustrated, others seemed demoralized by the unwarranted protraction of their year of study, payment of additional fees and levies as well as other avoidable expenditures thereof. The foregoing submissions demystifies strike and its effects on our public universities, and also calls for holistic and proactive approaches to mitigate the situation. Against this backdrop, the paper x-rayed the effects of strikes to advancement of education system vis-a-vis the sustainable socio-economic development of the nation, and as well recommends the way forward.